The fundamentals of scientific research an introductory laboratory manual - Kelly, Marcy A.; Haddix, Pryce L. (Hoboken, New Jersey John Wiley & Sons, Inc., 2015)
The Fundamentals of Scientific Research: An Introductory Laboratory Manual is a laboratory manual geared towards first semester undergraduates enrolled in general biology courses focusing on cell biology.
Includes bibliographical references (page 167) and index.
Keywords: Cytology -- Laboratory manuals